2023
DOI: 10.3390/nu15051238
|View full text |Cite
|
Sign up to set email alerts
|

Rationale, Design and Participants Baseline Characteristics of a Crossover Randomized Controlled Trial of the Effect of Replacing SSBs with NSBs versus Water on Glucose Tolerance, Gut Microbiome and Cardiometabolic Risk in Overweight or Obese Adult SSB Consumer: Strategies to Oppose SUGARS with Non-Nutritive Sweeteners or Water (STOP Sugars NOW) Trial and Ectopic Fat Sub-Study

Abstract: Background: Health authorities are near universal in their recommendation to replace sugar-sweetened beverages (SSBs) with water. Non-nutritive sweetened beverages (NSBs) are not as widely recommended as a replacement strategy due to a lack of established benefits and concerns they may induce glucose intolerance through changes in the gut microbiome. The STOP Sugars NOW trial aims to assess the effect of the substitution of NSBs (the “intended substitution”) versus water (the “standard of care substitution”) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 86 publications
0
2
0
1
Order By: Relevance
“…Eine kürzlich durchgeführte Meta-Analyse zeigte, dass eine Zunahme des Konsums von Getränken mit nicht-nutritiven Süßungsmitteln um eine Portion/Tag mit einem 13 %igen Anstieg des T2Dm-Risikos verbunden war [96]. Zudem zeigen jüngste Daten, dass Getränke mit nicht-nutritiven Süßungsmitteln als Ersatzstrategie empfohlen werden, obwohl ihre Vorteile noch umstritten sind und zu befürchten ist, dass sie durch Veränderungen des Darmmikrobioms eine Glukoseintoleranz hervorrufen könnten [97]. Süßungsmittel werden wegen ihrer verschiedenen chemischen Eigenschaften unterschiedlich verstoffwechselt, mit diversen Auswirkungen auf die Glukosehomöostase und die zugrundeliegenden Mechanismen, was die Ursache für die Unterschiede im Stoffwechselverhalten von Süßungsmitteln und die widersprüchlichen Ergebnisse sein kann [98].…”
Section: Erkenntnisse üBer Einzelne (Isolierte) Nährstoffeunclassified
“…Eine kürzlich durchgeführte Meta-Analyse zeigte, dass eine Zunahme des Konsums von Getränken mit nicht-nutritiven Süßungsmitteln um eine Portion/Tag mit einem 13 %igen Anstieg des T2Dm-Risikos verbunden war [96]. Zudem zeigen jüngste Daten, dass Getränke mit nicht-nutritiven Süßungsmitteln als Ersatzstrategie empfohlen werden, obwohl ihre Vorteile noch umstritten sind und zu befürchten ist, dass sie durch Veränderungen des Darmmikrobioms eine Glukoseintoleranz hervorrufen könnten [97]. Süßungsmittel werden wegen ihrer verschiedenen chemischen Eigenschaften unterschiedlich verstoffwechselt, mit diversen Auswirkungen auf die Glukosehomöostase und die zugrundeliegenden Mechanismen, was die Ursache für die Unterschiede im Stoffwechselverhalten von Süßungsmitteln und die widersprüchlichen Ergebnisse sein kann [98].…”
Section: Erkenntnisse üBer Einzelne (Isolierte) Nährstoffeunclassified
“…A recent meta-analysis showed that a one-serving/day increase in the consumption of beverages containing artificial sweeteners was associated with a 13 % increase in T2DM risk [96]. In addition, recent data show that beverages with artificial sweeteners are recommended as a substitute strategy, although their benefits are still controversial and it is feared that they could induce glucose intolerance through changes in the gut microbiome [97]. Artificial sweeteners are metabolized differently because of their different chemical properties, with various effects on glucose homeostasis and underlying mechanisms, which may be the cause of the differences in the metabolic behaviour of artificial sweeteners as well as the conflicting results [98].…”
Section: Commentmentioning
confidence: 99%
“…The National Health and Nutrition Examination Survey (NHANES) investigates a spectrum of added sugar sources, including brown sugar, sugarcane syrup, corn syrup, honey, molasses, and white sugar ( 7 , 8 ). Previous studies have demonstrated the association of added sugars with elevated risks of obesity ( 9 , 10 ), diabetes mellitus (DM), and cardiovascular disease (CVD) ( 11 ), which are intrinsically correlated with frailty. Despite previous studies focusing on factors precipitating frailty in the older adults, there is limited evidence revealing the association between added sugars and frailty in the general population.…”
Section: Introductionmentioning
confidence: 99%